The Importance of Organizational Culture as well as Transformational Leadership towards the Employee Performance at PT. KHMI via Motivation as a Mediation Variable - Masiyono, Masiyono; Mei Nur Widigdo, Aslam (Dinasti Publisher, 2022)
In this era of globalization, every company are required to provide with good performance. The decline in performance of PT. KHMI will be an interesting phenomenon to study. The research purposes was to discover the influence of organizational culture and transformational leadership towards the employees performance at PT. KHMI via motivation as a mediator. The research method used was quantitative based on causal relations. The data used were primary data that obtained from observation, interviews and questionnaires. The research sample are consisted of 120 people out of 170 employee populations of PT. KHMI. The sampling technique used was simple random sampling which proceeds by Partial Least Square (PLS) through Smart PLS software version 3.2.8. The results indicates that organizational culture and transformational leadership had a positive and significant influence towards the employee performance at PT. KHMI both directly or indirectly through motivation as a mediator.